Insecticide resistance in mosquitoes (Diptera: Culicidae): mechanisms, detection and monitoring in public health - FONSECA, IDALYD; QUIÑONES, MARTHA L. (Revista Colombiana de Entomología, 2005)
Among the most serious obstacles in vector control programs for human diseases is the development of resistance to the insecticides used. According to WHO, approximately 40% of the 506 medically important arthropods show some degree of insecticide resistance. Of these species, about 50% are species of mosquitoes that vector malaria, dengue, yellow fever and filariasis. The two principal mechanisms of insecticide resistance are alterations in the target site or an increase in the detoxification rate of the insecticide. Once resistance is detected in a vector population it is crucial to determine its molecular and biochemical basis. Identification of resistance mechanisms permits the selection of insecticides to use in control programs and the evaluation of potential development of resistance to alternative insecticides. This review presents basic information regarding the main mechanisms of insecticide resistance identified in mosquito vectors of human diseases and the methodologies most used to monitor and detect them.